COMPARATIVE ANALYSIS OF THE QUALITY OF GO-JEK AND GRAB SERVICES ON STUDENT SATISFACTION FROM THE BUSINESS ECONOMICS FACULTY OF THE INDONESIAN CHRISTIAN UNIVERSITY (Case Study On Active FEB UKI Students In Odd Semester 2020/2021) - Mangihut , Dicky Oloan; Sinaga, Sautman; Hutajulu , Fharel M (Universitas Kristen Indonesia, 2021)
The development of better technology helps transportation to develop its features to be more modern by creating an online transportation application. This research is quantitative in nature and the samples taken in this study are active FEB UKI students in the 2020/2021 odd semester as many as 100, and the data analysis used in this study is the likert scale, important performance analysis (level of suitability and cartesius diagrams), and the t – test and the variables used in this study are service quality and customer satisfaction Keywords : service quality and customer satisfaction